PREDICTING DIFFICULT INTUBATION IN ELECTIVE SURGICAL PATIENTS: THE ROLE OF BEDSIDE SONOGRAPHIC MEASUREMENTS - M. S., ASWIN; M. B., JAGADISH; MULAGUND, SUMANGALA (International Journal of Current Pharmaceutical Research, 2025)
Objective: Predicting difficult intubation remains a pivotal challenge in anesthesia, with traditional methods often failing to identify all at-risk patients. This study investigates the efficacy of bedside sonographic measurements as predictors of intubation difficulty in elective surgical patients. Methods: A prospective observational study was conducted at Gulbarga Institute of Medical Sciences, Kalaburagi, involving 60 adult elective surgery patients. Sonographic measurements, including hyomental distance, pre-epiglottic space, anterior soft tissue distance, and neck circumference were evaluated for their ability to predict difficult intubation. Results: The study found significant associations between all measured parameters and intubation difficulty. Specifically, shorter hyomental and pre-epiglottic spaces were strongly predictive of difficult intubations. Increased anterior soft tissue thickness and larger neck circumference were also linked to higher intubation difficulty. Conclusion: Bedside sonographic measurements provide a reliable method for predicting difficult intubations in elective surgical patients. Their integration into preoperative evaluations can significantly enhance the prediction and management of difficult airways.